2004
DOI: 10.1007/978-3-540-30539-2_27
|View full text |Cite
|
Sign up to set email alerts
|

On the Security of MOR Public Key Cryptosystem

Abstract: Abstract. For a finite group G to be used in the MOR public key cryptosystem, it is necessary that the discrete logarithm problem(DLP) over the inner automorphism group Inn(G) of G must be computationally hard to solve. In this paper, under the assumption that the special conjugacy problem of G is easy, we show that the complexity of the MOR system over G is about log |G| times larger than that of DLP over G in a generic sense. We also introduce a group-theoretic method, called the group extension, to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Since the black box group algorithms work in any group, they will work in the automorphism group too, see [9,Theorem 1]. We have no way to prevent that.…”
Section: Security Of the Proposed Mor Cryptosystemmentioning
confidence: 99%
“…Since the black box group algorithms work in any group, they will work in the automorphism group too, see [9,Theorem 1]. We have no way to prevent that.…”
Section: Security Of the Proposed Mor Cryptosystemmentioning
confidence: 99%
“…In this section we describe the MOR cryptosystem [1,6] as automorphisms of a finite group G, however it can be generalized to other finitely generated algebraic structures easily. A description and a critical analysis of the MOR cryptosystem is in [3] and the references there.…”
Section: The Mor Cryptosystemmentioning
confidence: 99%
“…In [4] the authors developed a central commutator attack ; they showed that inner automorphisms are not well suited for MOR cryptosystem; especially when the group is nilpotent.…”
Section: A Proposed Automorphism For the Mor Cryptosystemmentioning
confidence: 99%
“…The MOR cryptosystem has attracted a lot of attention and some well written papers [4,11,14]. In this article we propose a new group and a subgroup of the group of automorphisms for the MOR cryptosystem.…”
Section: Introductionmentioning
confidence: 99%